Comparison of the effects of pneumatic ankle-foot orthosis and posterior leaf spring ankle-foot orthosis on spatiotemporal parameters of gait and ankle range of motion in patients with stroke: a preliminary study - Hasti Mohri; Ali Poorghasem; Atefe Rahimi; Mohammad Hadadi (Shiraz University of Medical Sciences, 2020)
Background: Chronic stroke patients face impairment due to ankle dorsiflexor weakness that can influence their ankle kinematics and gait. The objective of this study was to compare the effects of a pneumonic ankle-foot orthosis (AFO) with those of a posterior leaf spring (PLS) AFO on the spatiotemporal parameters of gait and ankle range of motion in hemiplegic stroke patients. Methods: In this cross-sectional study, 5 participants with chronic stroke were tested during one session under three conditions: without orthosis, with pneumatic AFO, and with PLS-AFO. Spatiotemporal gait parameters and ankle joint range of motion were measured with a motion analysis system. Results: The results indicated that the pneumatic orthosis can improve gait speed in comparison with no orthotics (p = 0.04). No significant difference was seen regarding other evaluated spatiotemporal parameters and ankle range of motion under different orthotic conditions. Conclusion: The comparison of the immediate effects of the pneumatic ankle-foot orthosis and those of the posterior leaf spring ankle-foot orthosis showed that in comparison with no orthosis or with PLS-AFO, the pneumatic orthosis could improve gait speed, but had no effect on cadence, step length, or ankle range of motion in chronic stroke patients.